Soft Infrastructure in Urban and Regional Planning Research: Analyzing Undergraduate Final Project Trends in Commemorating 101 Years of Engineering Education in Indonesia - Ridwan Sutriadi (International Journal of Nusantara Islam, 2022)
This paper describes the trend of the final project at the Undergraduate Urban and Regional Planning Program, Bandung Institute of Technology, as the first planning school in Asia to commemorate 101 years of engineering education in Indonesia. The scope of the study is an analysis of the final project at the graduate program level for the last eleven years from 2010 to 2021. Moreover, reviewing the factors that influence research trends in urban and regional planning. Hence, to show the role of soft infrastructure as the key to the implementation of the latest planning concepts through infrastructure development, and the use of technology to accelerate regional and urban development in a sustainable manner in Indonesiathis is based on the finding that most students like the theme of infrastructure and transportation as well as the emergence of new favorite themes about big data, smart cities, as well as social media. This paper also proves that the global theme of soft infrastructure is indeed in the realm of engineering, and the theme of the final project going forward needs to push the theme of governance, which is still less attractive, as well as business processes, all of which represent soft infrastructure in the context of urban and regional planning.